2008
DOI: 10.1177/0011128708325051
|View full text |Cite
|
Sign up to set email alerts
|

Gangkill: An Exploratory Empirical Assessment of Gang Membership, Homicide Offending, and Prison Misconduct

Abstract: Extant research indicates that inmates with street gang history are prone for prison misconduct but that inmates convicted of homicide offenses are less likely to be noncompliant. No research has explored the interaction between street gang history and homicide offending. Based on official infraction data from 1,005 inmates selected from the Southwestern United States, the current study found that inmates with street gang history and convictions for homicide offenses were significantly involved in six types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 36 publications
12
78
0
1
Order By: Relevance
“…If the relationship between individual-level factors and serious assaults on staff were consistent with those characteristics identified from studies relying on inmate violence as more broadly defined, it is anticipated that these attacks would be disproportionately perpetrated by inmates who are younger (Berk, Kriegler, & Baek, 2006;Cooper & Werner, 1990;Harer & Steffensmeier, 1996;Wooldredge, 1991), male (Baskin, Sommers, & Steadman, 1991;Harer & Langan, 2001), Black (DeLisi, Berg, & Hochstetler, 2004Harer & Steffensmeier, 1996; but see Jiang & Fisher-Giorlando, 2002;Cunningham, Sorensen, Vigen, & Woods, 2010), lacking a high school diploma or GED (Cunningham, Sorensen, & Reidy, 2005;Cunningham & Sorensen, 2006;Harer & Langan, 2001), members of prison gangs (DeLisi et al, 2004;Drury & DeLisi, 2011;Gaes et al, 2002), serving longer sentences for violent crimes (Berk et al, 2006;Griffin & Hepburn, 2006;Huebner, 2003; but see Cunningham & Sorensen, 2006;, housed in higher custody levels (Cunningham & Sorensen, 2006;Worrall & Morris, in press), with prior prison terms Cunningham et al, 2005;Sorensen & Pilgrim, 2000; but see Cao, Zhoa, & Van Dine, 1997), and particularly those with prior histories of prison violence (Drury & DeLisi, 2010;Harer & Langan, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…If the relationship between individual-level factors and serious assaults on staff were consistent with those characteristics identified from studies relying on inmate violence as more broadly defined, it is anticipated that these attacks would be disproportionately perpetrated by inmates who are younger (Berk, Kriegler, & Baek, 2006;Cooper & Werner, 1990;Harer & Steffensmeier, 1996;Wooldredge, 1991), male (Baskin, Sommers, & Steadman, 1991;Harer & Langan, 2001), Black (DeLisi, Berg, & Hochstetler, 2004Harer & Steffensmeier, 1996; but see Jiang & Fisher-Giorlando, 2002;Cunningham, Sorensen, Vigen, & Woods, 2010), lacking a high school diploma or GED (Cunningham, Sorensen, & Reidy, 2005;Cunningham & Sorensen, 2006;Harer & Langan, 2001), members of prison gangs (DeLisi et al, 2004;Drury & DeLisi, 2011;Gaes et al, 2002), serving longer sentences for violent crimes (Berk et al, 2006;Griffin & Hepburn, 2006;Huebner, 2003; but see Cunningham & Sorensen, 2006;, housed in higher custody levels (Cunningham & Sorensen, 2006;Worrall & Morris, in press), with prior prison terms Cunningham et al, 2005;Sorensen & Pilgrim, 2000; but see Cao, Zhoa, & Van Dine, 1997), and particularly those with prior histories of prison violence (Drury & DeLisi, 2010;Harer & Langan, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…The most consistent predictor indicative of the deprivation perspective is prison gang membership. Repeatedly, researchers have shown that prison gang membership predicts violent behavior in prison (Cunningham & Sorensen, 2006b;2007;DeLisi et al, 2004;Drury & DeLisi, 2011;Gaes, Wallace, Gilman, Klein-Saffran & Suppa, 2002).…”
Section: The Deprivation Perspectivementioning
confidence: 99%
“…Being married, previously employed, and having attained higher levels of education were shown to reduce prison misconduct, as they do crime in the community Sampson & Laub, 1993). The level of involvement in, or affiliation with street or prison gangs, alternately, increased the likelihood of various types of violent rule infractions (Di Placido, Simon, Witte, Gu, & Wong, 2006;Drury & DeLisi, 2011;Gaes, Wallace, Gilman, Klein-Safran, & Suppa, 2002;Griffin & Hepburn, 2006). The extent to which gang members are involved in prison violence, however, can depend on security precautions and procedures employed by correctional systems to prevent gang-related violence (DeLisi, Berg, & Hochstetler, 2004).…”
Section: Community To Prison Behavioral Continuitymentioning
confidence: 99%